Optimizations of reinforcing particulates and processing parameters for stir casting of aluminium metal matrix composites for sustainable properties. (2022) - Kumar, Jatinder; Kumar, Vipan; Sharma, Shubham; Chohan, Jasgurpreet; Kumar, Raman; Singh, Sandeep; Obaid, Ahmed J.; Akram, Shaik Vaseem
Abstract: Due to its exceptional characteristics, aluminium matrix composites are used in defence, automotive, and structural applications. Stir casting for SiC and Gr reinforced AMCs was optimised. SiC weight was kept constant during manufacturing, while Gr was 1, 3, and 5% by weight. Stir casting was used to formulate AMCs by varying graphite amounts, stirring time, and stirring speed according to Taguchi's L9 OA. Hardness, tensile strength, and porosity levels of composites were examined. Taguchi analysis and Grey Relational Analysis optimised stir casting. Stirring speed, duration, and graphite content were found to affect AMC hardness. Graphite particles influence AMC strength more than stirring speed and time. GRA results show that include Gr in AMCs is the most important component impacting hybrid AMC characteristics, contributing 63.83 percent to optimal response values. Stirring speed and time contribute 17.27% and 11.1% to optimal response values. Comparing anticipated and experimental GRG validates results.